Efektivitas Model Pembelajaran Blended Learning pada Pembelajaran Tatap Muka Terbatas di Madrasah Ibtidaiyah - M. Arif Khoiruddin; Sutiani Sutiani (Intelektual: Jurnal Pendidikan dan Studi Keislaman, 2022)
The learning process during the COVID-19 pandemic requires many adjustments, sometimes creating new problems that face immediately. The case arises, so educators make various innovations to support the implementation of the teaching process. This study uses a qualitative approach to understand how the blended learning model at Madrasah Ibtidaiyah Islamiyah Nganjuk. Data collection techniques through observation, interviews, and documentation with data sources from the head of the madrasa, fathers and teachers, students and parents of students. The results explain blended learning effectively because of the availability of internet support facilities, computer laboratories, and ICT lessons taught since 2020. Students and parents also respond positively to the application of limited face-to-face learning by combining online through blended learning. Then teacher help because they can carry out direct interactions with their students even though the limit.